2024
DOI: 10.1159/000536559
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Depression and Inflammatory Biomarkers of Neutrophil-Lymphocyte Ratio, Platelet-Lymphocyte Ratio, and Monocyte-Lymphocyte Ratio: A Prospective Observational Study

Marco La Verde,
Mario Luciano,
Mario Fordellone
et al.

Abstract: Objectives: Postpartum depression (PPD) is a severe mental health disorder affecting a significant proportion of mothers, often undiagnosed and untreated, with potential long-term effects. While numerous studies have identified risk factors for PPD, the relationship between inflammatory markers and PPD remains unknown. This study aimed to investigate the potential correlation between indirect inflammatory markers, specifically neutrophil-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(56 reference statements)
0
0
0
Order By: Relevance
“…Our study aimed to investigate the diagnostic value of DFR in identifying PE in postpartum women. Previous studies have reported the predictive value of NLR or PLR on postpartum depression and poor neonatal prognosis [ 17 19 ]. Given that neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are simple biomarkers readily available from routine laboratory values, and may be useful components of PE risk prediction models, we would further investigate the diagnostic value of DFR combined with NLR or PLR in identifying PE in postpartum women.…”
Section: Introductionmentioning
confidence: 99%
“…Our study aimed to investigate the diagnostic value of DFR in identifying PE in postpartum women. Previous studies have reported the predictive value of NLR or PLR on postpartum depression and poor neonatal prognosis [ 17 19 ]. Given that neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are simple biomarkers readily available from routine laboratory values, and may be useful components of PE risk prediction models, we would further investigate the diagnostic value of DFR combined with NLR or PLR in identifying PE in postpartum women.…”
Section: Introductionmentioning
confidence: 99%